Firstly, $3.99 × 5 = $19.95
Second, $2.75 × 5 = $13.75
Third, $2.70 × 3 = $8.1 (Since it is just $8.1 that won't make sense so we'd add a 0 so It's $8.10.)
Then we do the last one which is 13 × $0.89 = $11.57.
So now since we are done multiplying we can add it all up.
The answer is $53.37 when we finish adding it up.
and I don't know what A number sentence is sorry :(
I took a long time typing this :< I hope this helps though! :D
Hi there!
(3/2)2+4<span>÷2*3 = 9
Hope this helps! :)</span>
Los gramos son más de miligramos
Answer:
(x -6)^2 +(y -3)^2 = 2
Step-by-step explanation:
The midpoint (C) is the center of the circle:
C = ((5, 4) +(7, 2))/2 = ((5+7)/2, (4+2)/2) = (6, 3)
A circle with center (h, k) that goes through point (a, b) can be written as ...
(x -h)^2 +(y -k) ^2 = (a -h)^2 +(b -k)^2
Using the values for this problem, we get ...
(x -6)^2 +(y -3)^2 = (5 -6)^2 +(4 -3)^2
(x -6)^2 +(y -3)^2 = 2
Answer:
A. Sheila lives closer to the library
Step-by-step explanation: